The genus Labania Hedqvist 1963 (Hymenoptera, Braconidae: Doryctinae) with description of a new species from Brazil - Bortoni, Marco Aurélio; Castro, Clóvis Sormus De; Penteado-Dias, Angélica Maria (Zootaxa, 2015)
In this paper a new species of doryctine wasp of the small and rarely collected genus Labania Hedqvist (Braconidae: Doryctinae) is described and illustrated from Brazil. Labania carolinae sp.n. is similar to Labania minuta Marsh, but it can be easily distinguished by the head yellow, with stemmaticum black, mesosoma and metasoma yellow, legs whitish yellow, propodeum with distinct areola, fore wing vein 1cu-a interstitial with 1M, and long ovipositor.